Related F-box proteins control cell death in Caenorhabditis elegans and human lymphoma - Chiorazzi, Michael (2013)
Cell death is a common metazoan cell fate, and its inactivation is central to human malignancy. In Caenorhabditis elegans, apoptotic cell death occurs via the activation of the caspase CED-3 following binding of the EGL-1/BH3-only protein to the antiapoptotic CED-9/ BCL2 protein. Here we report a major alternative mechanism for caspase activation in vivo involving the F-box protein DRE-1. DRE-1 functions in parallel to EGL-1, requires CED-9 for activity, and binds to CED-9, suggesting that DRE-1 promotes apoptosis by inactivating CED-9. FBXO10, a human protein related to DRE-1, binds BCL2 and promotes its degradation, thereby initiating cell death. Moreover, some human diffuse large B-cell lymphomas have inactivating mutations in FBXO10 or express FBXO10 at low levels. Our results suggest that DRE-1/FBXO10 is a conserved regulator of apoptosis.